Phenolic Compound Analysis and Antioxidant Properties of O. Alborosea - Erim, Kader; Savcı, Ahmet (My University, 2024)
The Onosma genus has been used as a treatment among the public for a long time. In this study, the content analysis and some biological activities of the plant O. Alborosea Fisch. & C.A.Mey. ssp. (O. alborosea) used in traditional medicine in our country were investigated. For this purpose, methanol and water extracts of the plant were taken and the total phenolic substance amount of each extract was determined by HPLC device. FRAP, CUPRAC reduction methods and DPPH, ABTS radical scavenging methods were used to determine antioxidant activities. According to the results of our study, it was determined that water and methanol extracts showed lower activity compared to standard antioxidants. It can be said that the reason for this is related to the ratio of the phenolic amount they contain. Since no antioxidant studies were found when the literature search related to the current plant species was conducted, it is thought that our study will guide other studies to be carried out with this plant species and is important in terms of protecting our plants, which are our genetic treasure, and transferring them to future generations.
Keywords: Muş, Antioxidant, Phenolic Substance, Free Radical, O. Alborosea